2017
DOI: 10.1016/j.ijheatmasstransfer.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal energy storage enhancement of a binary molten salt via in-situ produced nanoparticles

Abstract: Thermal energy storage (TES) system is an essential component of any concentrating solar thermal power (CSP) plant to ensure a reliable plant operation even at night or cloudy weather. To enhance the TES capacity, a one-step method was proposed to synthesize nano-salts by in-situ production of CuO nanoparticles, via a high temperature decomposition of copper oxalate, in a binary salt used as a phase change material (PCM). The specific heat of the nano-salt both for solid and liquid phases were measured by diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Qiao et al reported numerical and experimental results for enhancing the specific heat of a binary nitrate salt mixture [34]. In 2017, Luo et al reported that the mixture of sodium nitrate and potassium nitrate was enhanced by CuO nanoparticles that are produced in situ via the high-temperature decomposition of copper oxalate with the nitrate salt mixture [35]. Most recently, in situ synthesized MgO nanoparticles enhanced the specific heat of a nitrate salt by up to 118% in the solid phase and 168% in the liquid phase [36].…”
Section: Introductionmentioning
confidence: 99%
“…Qiao et al reported numerical and experimental results for enhancing the specific heat of a binary nitrate salt mixture [34]. In 2017, Luo et al reported that the mixture of sodium nitrate and potassium nitrate was enhanced by CuO nanoparticles that are produced in situ via the high-temperature decomposition of copper oxalate with the nitrate salt mixture [35]. Most recently, in situ synthesized MgO nanoparticles enhanced the specific heat of a nitrate salt by up to 118% in the solid phase and 168% in the liquid phase [36].…”
Section: Introductionmentioning
confidence: 99%
“…For other samples with nanoparticles, the values of heat fusion are even lower than that of the base salt. The negative influence on fusion heat was also observed in the studies by Luo et al and Gimenez‐Gavarrell et al The variation of fusion heat is related to the formation of nanostructure around the particles. The nanostructure and its number are different for different size nanoparticles at the same mass concentration because of its different distribution characteristics in the base salt.…”
Section: Resultsmentioning
confidence: 99%
“…However, some undesirable properties set a limitation on further applications of molten salts. Researchers have attempted to improve thermal performance by adding nanoparticles into molten salts, in order to formulate new nanofluids as working media, and excellent thermal storage characteristics have been obtained . Shin and Banerjee doped SiO 2 nanoparticles into carbonate salt and obtained enhancement of 5–15% and 25–28% for specific heat and thermal diffusivity, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have attempted to improve thermal performance by adding nanoparticles into molten salts, in order to formulate new nanofluids as working media, and excellent thermal storage characteristics have been obtained. [15][16][17][18] Shin and Banerjee 19 doped SiO 2 nanoparticles into carbonate salt and obtained enhancement of 5-15% and 25-28% for specific heat and thermal diffusivity, respectively. Awad et al 20 investigated the thermophysical properties of nitrate salt with various nanoparticles.…”
Section: Introductionmentioning
confidence: 99%